Relative abundance and size composition of prey in the common minke whale diet in selected areas of the northeastern Atlantic during 2000-04 - Windsland, Kristin; Lindstrom, Ulf; Tormod Nilssen, Kjell; Haug, Tore (J. Cetacean Res. Manage., 2023)
A total of 210 common minke whales (Balaenoptera acutorostrata) were sampled in five different areas in the northeastern Atlantic during May-June 2000-04. Analysis of forestomach contents revealed a relatively mixed diet at the population level, whereas on an individual level, each whale had fed upon mainly one species. There were significant differences in diet composition between areas and some differences between years. The importance of krill in the Barents Sea increased with latitude and krill dominated the Spitsbergen diet. Capelin dominated the diet around Bear Island and contributed considerably to the diet along the coast of northern Norway. In the latter area, herring and haddock were also a great part of the diet. The diet in the Norwegian Sea consisted of mainly mature herring, while the diet in the North Sea was dominated by sand eels and mackerel. The minke whales were found to feed on a wide range of prey sizes, apparently determined by the availability of different size classes.